Aortic counterpulsation in cardiogenic shock during acute myocardial infarction. (July 2014) - Rognoni, Andrea; Cavallino, Chiara; Lupi, Alessandro; Veia, Alessia; Rosso, Roberta; Rametta, Francesco; Bongo, Angelo Sante
<x xml:space="preserve">Abstract</x> Intra-aortic balloon counterpulsation is the most widely used form of mechanical hemodynamic support in the setting of cardiogenic shock due to ST-segment elevation myocardial infarction (STEMI). Intra-aortic balloon pump (IABP) is also strongly recommended (class 1b) in the current European guidelines for treatment of STEMI. The evidence of a possible benefit of IABP in this setting is based mainly on registry data and a few randomized trials. Cardiogenic shock and subsequent death due to STEMI result from three factors: hemodynamic deterioration, occurrence of multiorgan dysfunction and systemic inflammatory response. IABP does not cause an immediate improvement in blood pressure, but the recent SHOCK II trial shows positive effects on multiorgan dysfunction. Some experimental and clinical studies have indicated that IABP results in hemodynamic benefits as a result of afterload reduction and diastolic augmentation with improvement of coronary perfusion. However, the effect on cardiac output is modest and may not be sufficient to reduce mortality. Furthermore we can say that the use of IABP before coronary revascularization in the setting of STEMI complicated with cardiogenic shock may make the interventional procedure safer by improving left ventricular unloading. The purpose of the present review is to clarify the state of the art on this topic.